Surgical Management of a Coronary-Bronchial Artery Fistula Combined with Myocardial Ischemia Revealed by (13)N-Ammonia Positron Emission Tomography - Choi, Hang Jun (Korean J Thorac Cardiovasc Surg, 2017)
A 71-year-old male with known bronchiectasis and atrial fibrillation was admitted to Seoul St. Mary’s Hospital with recurrent transient ischemic attack. Radiofrequency ablation was performed to resolve the patient’s atrial fibrillation, but failed. However, a fistula between the left circumflex artery and the bilateral bronchial arteries was found on computed tomography. Fistula ligation and a left-side maze operation were planned due to his recurrent symptom of dizziness, and these procedures were successfully performed. After the operation, the fistula was completely divided and no recurrence of atrial fibrillation took place. A coronary-bronchial artery fistula is a rare anomaly, and can be safely treated by surgical repair.